TANGGUNG JAWAB PEMERINTAH DAERAH PADA PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA MENUJU NEGARA KESEJAHTERAAN - Ferricha, Dian (IAIN Tulungagung, 2016)
Local government autonomy becomes an important moment to reflectthe achievement of the nation development especially in immigrantworker protection. A good protection system will give a guarantee andcertainty not only to the workers themselves but also to their familiesat home when they work overseas. The protection system should coverthe pre-departure, the placement, and the repatriation. The RegulationNumber 9 Year 2015 on Local Government open new hope for the localgovernment to construct a good protection and placement system forthe Indonesian immigrant workers since they are still at home.Kata kunci: Tanggungjawab, Pemerintahan Daerah, Tenaga KerjaIndonesia, Negara